Diet of the chola guitarfish, Rhinobatos percellens (Rhinobatidae), in the Paranaguá Estuarine complex - Carmo,Wanessa P.D. do (2015)
The chola guitarfish, Rhinobatos percellens, is one of the most-captured batoids on the Brazilian coast, and an important predator of benthic community. Stomachs from R. percellens were sampled in the Paranaguá estuarine complex (March/2006 to March/2007 and October/2008 to September/2009). The stomachs obtained were used for describing the diet of R. percellens, and verifying if there are seasonal and ontogenetic differences in their feeding into the estuarine area. The general analysis showed a specialized diet with a predominance of three species in food contents: Leptochela serratorbita, Caridea remains and Ogyrides alphaerostris. Ontogenetic and seasonal analysis did not reveal significant differences in the food consumption. These data reveal that R. percellens is a specialist predator of L. serratorbita, and this food component is consumed by all size classes.